(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Bharati Mukherjee is one of the true authors of the Indian Diaspora, having achieved a fortunate position within a relatively brief creative journey. She has captured the Indian immigrant involvement in her works and two collections of short fiction as an exile in the United States. She is an author, short story essayist, verified essayist, and writer who was born in India. The vast bulk of her writings are about the lives of Indian immigrants in the United States. She investigates the topic of movement and change in her books. Immigrants, too, have one desire: to live in America for the rest of their lives. As a result, as immigrants, they go through a process of transition and identity transformation. She passes through distinct stages, such as exile, progress, and migration. Her paintings reveal her conflicts with the ethos, cultures, and people of the country where she was born (India) and the one to which she emigrated (Canada) (America). In all of her works, the nature of societal conflict causing mental urgency forms the core of her achievement as a creative craftsman. She is succeeding in portraying societal conflict between the East and the West as a mental crises in her heroes’ own psyche. Mukherjee focuses on sensitive female protagonists who require a stable sense of personal and societal identity. She is concerned about her hero’s survival in the new surroundings. She is concerned in conveying a clear and interesting picture of Indian life to the American audience.